Novel Catalysts Based on Synthetic Mesoporous Silicates of the MCM-41 Type and Hydroxyapatite for Desulfurization of Model Fuel - Nadezhda O. Donskaya; Margarita A. Goldberg; Alexander S. Fomin; Anna O. Koptelova; Polina D. Domashkina; Ekaterina A. Eseva; Olga S. Antonova; Anatoliy A. Konovalov; Alexander V. Leonov; Egor A. Kudryavtsev; Fadis F. Murzakhanov; Marat R. Gafurov; et al. (Ceramics, 2025)
Nanopowders of hydroxyapatite (HA) and Fe-substituted hydroxyapatite (HAFe) were synthesized by wet precipitation on either MCM-41 (a synthetic, mesoporous aluminosilicate material) or an aluminum-containing MCM-41 (AlMCM) support. According to X-ray diffraction data, all of the synthesized materials are composite powders consisting of amorphous silicate and an HA phase with low crystallinity. The presence of aluminum and iron in the structure of the powders resulted in further amorphization. The obtained samples showed high specific surface areas (SSAs), ranging from 162.3 to 186.6 m2/g for MCM-41-HA and from 112.6 to 127.2 m2/g for AlMCM-HA. The hysteresis loops were found to be of type H3, indicating the formation of slit-like pores in the intercrystalline space, as confirmed by transmission electron microscopy, which revealed the presence of lamellar and flake-like particles. Catalytic activity tests showed that the conversion of dibenzothiophene depended on the iron concentration in the material and the acidity of the support. To further improve the catalytic activity of the materials, they were impregnated with molybdenum compounds. Active molybdenum peroxo complexes formed under these conditions enabled 100% conversion of dibenzothiophene. To our knowledge, this is the first study on the influence of MCM-41-HA- or AlMCM-HA-based materials on dibenzothiophene conversion via oxidative desulfurization using hydrogen peroxide as an oxidant.